A Theory of Delegated Contracting - Wolfgang Gick (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Delegated contracting describes a widely observable vertical contractual relationship where a top principal (program designer) hires an intermediary to offer a predesigned screening contract to a downstream agent who should produce a quantity depending on his true marginal cost type. The principal has no direct access to the downstream agent and utilizes budgeting in the sequence of contracts. This paper proposes a general theory of delegated contracting where information acquisition is limited to the (sub-)contract offer stage. To reach delegation proofness, the principal designs information rents accordingly. The solution concept follows the convexity of rent pro le. The paper shows that the optimal contract is fully separating over the subcontracting interval, leading to strictly decreasing output targets.
Keywords: D23; D73; L51; 330